The Role of Investment Understanding in Moderating the Effect of Financial Literacy, Risk Perception and Investment Motivation on Student Interest to Invest in the Capital Market: Peran Pemahaman Investasi dalam Memoderasi Pengaruh Literasi Keuangan, Persepsi Risiko dan Motivasi Investasi Terhadap Minat Mahasiswa Untuk Berinvestasi di Pasar Modal - Assari, Putri Ayu; Hariyanto, Wiwit (Indonesian Journal of Innovation Studies, 2022)
This research aims to find out the role of investment understanding in moderating the influence of financial literacy, risk perception and investment motivation on student’s interest in investing in capital markets. The selection of samples is done by metode purposive sampling. Sampel used as many as 100 respondents. The spread of questionnaires was conducted with google form distributed to 100 accounting students in semesters 6 and 8 of Muhammadiyah University of Sidoarjo. Data analysis is done with the help of Smart PLS 3.0 application. Data analysis is carried out in two ways, namely the Outer Model for data validity and reliability test. Next is the Inner Model for hypothesis test. The results of the study indicate that investment understanding cannot moderate the influence of investment motivation on student’s investment interests in the capital market.